The effect of interface morphology in waste tyre rubber powder filled elastomeric matrices on the tear and abrasion resistance - D. H. Abang Ismawi Hassim; F. Abraham; J. Summerscales; P. Brown (eXPRESS Polymer Letters)
The interface between either Micronised Rubber Powder (MRP) or Crumb Rubber Powder (CRP) fillers in either Natural Rubber (NR) or Butadiene Rubber (BR) matrices has been studied using Transmission Electron Microscopy (TEM) ‘network visualisation’. The convoluted structure of CRP provides better interfacial adhesion than MRP. The weak interface between the MRP networks and the rubber matrix was confirmed by the lower physical bonding. The crescent tear strength test was able to characterise the possible weak interaction of MRP in unfilled NR or NR/BR blend matrix. The Akron test was used for carbon black-filled matrix.